2016
DOI: 10.1155/2016/3674946
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hemoglobin Concentration Is Associated with Retinal Ischemia and the Severity of Diabetic Retinopathy in Type 2 Diabetes

Abstract: Aims. To assess the association of blood oxygen-transport capacity variables with the prevalence of diabetic retinopathy (DR), retinal ischemia, and macular oedema in patients with type 2 diabetes mellitus (T2DM). Methods. Cross-sectional, case-control study (N = 312) with T2DM: 153 individuals with DR and 159 individuals with no DR. Participants were classified according to the severity of DR and the presence of retinal ischemia or macular oedema. Hematological variables were collected by standardized methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…All patients received a full ophthalmologic examination that included visual acuity, slit-lamp examination and indirect fundoscopic examination. A diagnosis of PDR, non-PDR or AMD was reached according to fundus fluorescein angiography (FFA) and SD-OCT (Heidelberg Engineering OCT 2 Module 85.000Hz) findings after detailed direct and indirect fundus examinations on dilated pupillae (Ambati et al, 2012;Čolak et al, 2017;Colijn et al, 2019;Paun et al, 2015;Boekhoorn et al, 2007;Prakash et al, 2017;Traveset et al, 2016;Magri et al, 2012). The control group were recruited from employees of the our hospital, their relatives and who were without any signs of AMD, DRP our ophthalmology department out of patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received a full ophthalmologic examination that included visual acuity, slit-lamp examination and indirect fundoscopic examination. A diagnosis of PDR, non-PDR or AMD was reached according to fundus fluorescein angiography (FFA) and SD-OCT (Heidelberg Engineering OCT 2 Module 85.000Hz) findings after detailed direct and indirect fundus examinations on dilated pupillae (Ambati et al, 2012;Čolak et al, 2017;Colijn et al, 2019;Paun et al, 2015;Boekhoorn et al, 2007;Prakash et al, 2017;Traveset et al, 2016;Magri et al, 2012). The control group were recruited from employees of the our hospital, their relatives and who were without any signs of AMD, DRP our ophthalmology department out of patients.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are cross-sectional studies reporting that there may be a relationship between the variability in serum biochemical parameters, serum lipoproteins, inflammatory markers, CBC parameters and the risk of DR and AMD (Colijn et al, 2019;Paun et al, 2015;Boekhoorn et al, 2017;Prakash et al, 2017;Traveset et al, 2016). However, epidemiological data have been inconsistent regarding the associations of CRP, CBC parameters, serum lipid levels, DR and AMD (Colijn et al, 2019;Paun et al, 2015;Boekhoorn et al, 2007;Prakash et al, 2017;Traveset, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing studies reported that routine blood examination could provide rich and effective information to assist risk strati cation of disease [10][11].The promising index neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) conveyed a systematic in ammatory response in our body and has been evidenced as predictive and prognostic factors for DM and the related complications [12][13][14][15]. Moreover, Hemoglobin (Hb) was also a well-established biomarker for DR [16][17]. However, the association between these factors and DR among patients without diabetes or hypertension family history remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since the metabolism in the retina is profoundly active, the tolerance of retinal cells to ischemia and hypoxia is poor. Therefore, the mechanisms of retinal ischemia and anti-injury protection have always been the hot topics in the field of DR pathogenesis [10,14,15]. Despite a large number of basic experiments and clinical studies at home and abroad, there is still no effective means of prevention, early intervention, and treatment of DR.…”
Section: Introductionmentioning
confidence: 99%